POLA KOMUNIKASI PIMPINAN PONDOK MODERN DARUSSALAM GONTOR PUTRI 4 DALAM MEMBANGUN KOMUNIKASI SOSIAL (STUDI PADA MASYARAKAT DESA LAMOMEA KECAMATAN KONDA KABUPATEN KONAWE SELATAN) - Herysanti Agra Setiawati (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2016)
Abstract The problem in this research are: 1) How Leadership Communication Patterns Pondok Modern Darussalam Gontor Princess 4. 2) How Social Communications Pondok Modern Darussalam Women Gontor 4 in the Village District of Konda Konawe Lamomea South. The purpose of this study are: 1) To Know How Communication Patterns head of Pondok Modern Darussalam Gontor Quarterfinal 4, 2) To Learn How Social Communications Pondok Modern Darussalam Gontor daughter Lamomea Subdistrict 4 in the village of Konda Konsel. This study uses a model of communication proposed by Harold Lasswell (Forsdale 1981). This study is a qualitative study, using purposive sampling techniques. The location of this research was conducted in Pondok Modern Darussalam Gontor Princess 4 Lamomea Village District of Konda Konsel. With the number of informants as many as 10 people, the head of Pondok Modern Darussalam Gontor Quarterfinal 4, Pembina santriwati, Uztadzah, santriwati, Religious Leaders and Community Leaders. The data used descriptive qualitative method. The results showed that the pattern of Communication Leaders Pondok Modern Darussalam Gontor Princess 4 ie Communication Patterns two-way or reciprocal (Two way traffic communication) in which the pattern of this communication, communicators and communicants into exchange functions in living their functions, communicators in the first phase be communicant and at a later stage function interchangeably. Communicators here is the head of Pondok Modern Darussalam Gontor daughter is 4 and a communicant of Trustees santriwati, uztadzah and female students as a communicant which is internal boarding school and the community as a communicator external boarding school. And social communication Pondok Modern Darussalam Gontor Princess 4 with the public is through competitions taklim conducted annually and involve mothers taklim, salat Eid and pray Eid al-Adha together in the boarding school in each year and study jointly conducted by villagers and mothers taklim cooperate with the Pondok Modern Darussalam Gontor Princess 4 is done every week. Through modern communication patterns leaders cottage Darussalam Gontor daughters 4 and through the social communication, creating social relationships that will generate a sense of kinship and familiarity between Pondok Modern Darussalam Gontor daughter Lamomea 4 and the village community. Keywords: Communication Patterns, Boarding School, Social Communications